Government Budgeting and Expenditure Controls : Theory and Practice - Premchand, A. (International Monetary Fund, 1989)
This book, written by A. Premchand, offers a comprehensive review of fiscal policies and their implications for budgeting and expenditure controls. It provides an in-depth discussion of techniques, procedures, and processes of budgeting with illustrative material drawn from the experiences of industrial and developing countries.